Color Conceptosphere of the Story “Meshcherskaya Side” by K. Paustovsky (Proceedings of Southern Federal University. Philology, 2021)
Tatyana V. Sivova (Grodno, Republic of Belarus)The purpose of the article is to reconstruct a fragment of K. Paustovsky’s coloristic picture of the world on the material of the story “Mescherskaya side”, which had not previously become the subject of special research carried out from the standpoint of linguistics of color, which determines the scientific novelty of this work. The research methodology is based on the descriptive and analytical method, the method of compatibility analysis, the method of contextual analysis, quantitative data processing. As the result of the research 1) the composition of color concepts, actualized by the writer in color chronotope creation, was revealed; only the color core of the story is represented by 24 color terms; 2) the dominants of the story color spectrum (black, green, gray) were determined; this color sequence is unique: it is recorded in Paustovsky’s works for the first time; 3) the color dominants denotative spheres (predominantly nature, artifacts, man) were established; 4) the functional potential of color terms was described; it includes the ontological function, the species function, the terminological function, as well as the function of temporal meaning transfer, the evaluative function, the aestheticization one; 5) the individual author’s specificity of artistic perception and reality coloristic visualization was revealed; among the significant color individual features are multicolor effect, non-stereotyped color characteristics, color associativity. The results obtained make it possible to create a comprehensive description of the story’s color conceptosphere. Key words: linguistics of color, color term, concept, writer’s language, individual writing style.DOI 10.18522/1995-0640-2021-2-54-66